The sodium-glucose co-transporter 2 inhibitor velagliflozin reduces hyperinsulinemia and prevents laminitis in insulin-dysregulated ponies - Meier, Alexandra (PLoS One, 2018)
There are no registered veterinary drugs for treating insulin dysregulation and preventing insulin-associated laminitis in horses. Velagliflozin is a sodium-glucose co-transport 2 inhibitor that reduces renal glucose reabsorption, promotes glucosuria, and consequently, decreases blood glucose and insulin concentrations. This study aimed to determine if velagliflozin reduced hyperinsulinemia and prevented laminitis in insulin-dysregulated ponies fed a challenge diet high in non-structural carbohydrates (NSC). An oral glucose test (1 g dextrose/kg BW) was used to screen 75 ponies for insulin dysregulation, of which 49 ponies with the highest insulin concentrations were selected. These animals were assigned randomly to either a treated group (n = 12) that received velagliflozin (0.3 mg/kg BW, p.o., s.i.d.) throughout the study, or a control group (n = 37). All ponies were fed a maintenance diet of alfalfa hay for 3 weeks, before transferring to a challenge diet (12 g NSC/kg BW/d) for up to 18 d. Blood glucose and serum insulin concentrations were measured over 4 h after feeding, on d 2 of the diet. The maximum glucose concentration was 22% lower (P = 0.014) in treated animals, with a geometric mean (95% CI) of 9.4 (8.0–11.0) mM, versus 12.1 (10.7–13.7) mM in the controls. This was reflected by lower (45%) maximum insulin concentrations in the treated group (P = 0.017), of 149 (97–228) μIU/mL, versus 272 (207–356) μIU/mL for controls. The diet induced Obel grade 1 or 2 laminitis in 14 of the 37 controls (38%), whereas no velagliflozin-treated pony developed laminitis (P = 0.011). Velagliflozin was well-tolerated, with no hypoglycemia or any clinical signs of adverse effects. The main limitation of this study was the sample size. Velagliflozin shows promise as a safe and effective compound for treating insulin dysregulation and preventing laminitis by reducing the hyperinsulinemic response to dietary NSC.